Facilitators and barriers impacting in-hospital Trauma Quality Improvement Program (TQIP) implementation across country income levels: a scoping review - Yue Sun; Martin Gerdin Wärnberg; Johanna Berg; George Kapanadze (BMJ Open)
Objective Trauma is a leading cause of mortality and morbidity globally, disproportionately affecting low/middle-income countries (LMICs). Understanding the factors determining implementation success for in-hospital Trauma Quality Improvement Programs (TQIPs) is critical to reducing the global trauma burden. We synthesised topical literature to identify key facilitators and barriers to in-hospital TQIP implementation across country income levels.Design Scoping review.Data sources PubMed, Web of Science and Global Index Medicus databases were searched from June 2009 to January 2022.Eligibility criteria Published literature involving any study design, written in English and evaluating any implemented in-hospital quality improvement programme in trauma populations worldwide. Literature that was non-English, unpublished and involved non-hospital TQIPs was excluded.Data extraction and synthesis Two reviewers completed a three-stage screening process using Covidence, with any discrepancies resolved through a third reviewer. Content analysis using the Consolidated Framework for Implementation Research identified facilitator and barrier themes for in-hospital TQIP implementation.Results Twenty-eight studies met the eligibility criteria from 3923 studies identified. The most discussed in-hospital TQIPs in included literature were trauma registries. Facilitators and barriers were similar across all country income levels. The main facilitator themes identified were the prioritisation of staff education and training, strengthening stakeholder dialogue and providing standardised best-practice guidelines. The key barrier theme identified in LMICs was poor data quality, while high-income countries (HICs) had reduced communication across professional hierarchies.Conclusions Stakeholder prioritisation of in-hospital TQIPs, along with increased knowledge and consensus of trauma care best practices, are essential efforts to reduce the global trauma burden. The primary focus of future studies on in-hospital TQIPs in LMICs should target improving registry data quality, while interventions in HICs should target strengthening communication channels between healthcare professionals.